MANAGEMENT OF THE PRODUCTION RESOURCES OF ENTERPRISE BASED ON FINANCIAL MOTIVATION OF THE PERSONNEL: THEORETICAL ASPECT - O. Gaponenko; M. Mashchenko; O. Klimenko; N. Stepanenko; О. Sergienko (Фінансово-кредитна діяльність: проблеми теорії та практики, 2021)
Abstract. The article deals with theoretical and organizational aspects of the management justification on the basis of the effective financial motivation of the personnel in the context of its influence to use the production resources of the enterprise. To determine the studied object, the influence of the financial motivation of the personnel, the content of the category «effectiveness of financial motivation» is disclosed; the methods of the financial motivation are characterized; the types of the production resources of the enterprise are presented. Generalization of the provisions makes it possible to characterize the effectiveness of the financial motivation of the staff in two main areas: providing salaries and other bonuses in accordance with the quantity and quality of the labor results as well as the labor cost in the labor market; enhancing the employer’s growth: the labor productivity as well as the absolute indicators of income, profit on 1 UAH of salary (salary-making).